2019
DOI: 10.1038/s41561-019-0325-7
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous lower-mantle anisotropy beneath subduction zones

Abstract: Seismic anisotropy provides key information to map the trajectories of mantle flow and understand the evolution of our planet. While the presence of anisotropy in the uppermost mantle is well-established, the existence and nature of anisotropy in the transition zone and uppermost lower mantle are still debated. Here we use 3-D global seismic tomography images based on a large data set sensitive to this region to show the ubiquitous presence of anisotropy in the lower mantle beneath subduction zones. Whereas ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 59 publications
4
65
0
Order By: Relevance
“…The use of huge data sets and, notably, a large number of surface wave overtone dispersion measurements has led to an improved agreement between models. Chang et al () quantitatively compared recent models and found (i) an improved correlation between SGLOBE‐rani (Chang et al, ) and savani (Auer et al, ) of 0.5; this is an encouraging improvement compared to previous studies, which do not show correlations larger than 0.3; (ii) fast‐SV radial anisotropy anomalies in the transition zone in SGLOBE‐rani near subducted slabs, which also appear in some other models (e.g., savani and SEMUCB‐WM1, French & Romanowicz, ); and (iii) fast‐SH radial anisotropy anomalies in the ULM in SGLOBE‐rani near subducted slabs (Ferreira et al, ), which also appear in savani and seem consistent with shear‐wave splitting analyses. Given this increasing volume of observations, it is timely to investigate the origin of anisotropy in the mid‐mantle with geodynamic simulations and mantle fabrics calculations, which is the focus of this study.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…The use of huge data sets and, notably, a large number of surface wave overtone dispersion measurements has led to an improved agreement between models. Chang et al () quantitatively compared recent models and found (i) an improved correlation between SGLOBE‐rani (Chang et al, ) and savani (Auer et al, ) of 0.5; this is an encouraging improvement compared to previous studies, which do not show correlations larger than 0.3; (ii) fast‐SV radial anisotropy anomalies in the transition zone in SGLOBE‐rani near subducted slabs, which also appear in some other models (e.g., savani and SEMUCB‐WM1, French & Romanowicz, ); and (iii) fast‐SH radial anisotropy anomalies in the ULM in SGLOBE‐rani near subducted slabs (Ferreira et al, ), which also appear in savani and seem consistent with shear‐wave splitting analyses. Given this increasing volume of observations, it is timely to investigate the origin of anisotropy in the mid‐mantle with geodynamic simulations and mantle fabrics calculations, which is the focus of this study.…”
Section: Introductionmentioning
confidence: 85%
“…It has been reported that bridgmanite has a single‐crystal V S anisotropy of 33% at ambient conditions (Yeganeh‐Haeri, ), but that it decreases to 8% at 1,000‐km depth when using the extrapolated temperature and pressure derivatives of Wentzcovitch et al (). Such estimates of bridgmanite single‐crystal V S anisotropy have been shown to be even larger when considering elastic properties calculated by Zhang et al () (Ferreira et al, ). Ferropericlase, constituting 16% of the lower mantle, remains nearly isotropic at 660‐km depth, but its single‐crystal V S anisotropy increases considerably with pressure, becoming up to 40% in the D” region (Marquardt et al, ).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations